Considering Critical Factors of Li‐rich Cathode and Si Anode Materials for Practical Li‐ion Cell Applications. Issue 33 (24th June 2015) - Ko, Minseong; Oh, Pilgun; Chae, Sujong; Cho, Woongrae; Cho, Jaephil
<x xml:space="preserve">Abstract</x> In order to keep pace with increasing energy demands for advanced electronic devices and to achieve commercialization of electric vehicles and energy‐storage systems, improvements in high‐energy battery technologies are required. Among the various types of batteries, lithium ion batteries (LIBs) are among the most well‐developed and commercialized of energy‐storage systems. LIBs with Si anodes and Li‐rich cathodes are one of the most promising alternative electrode materials for next‐generation, high‐energy batteries. Si and Li‐rich materials exhibit high reversible capacities of <2000 mAh g−1 and >240 mAh g‐1, respectively. However, both materials have intrinsic drawbacks and practical limitations that prevent them from being utilized directly as active materials in high‐energy LIBs. Examples for Li‐rich materials include phase distortion during cycling and side reactions caused by the electrolyte at the surface, and for Si, large volume changes during cycling and low conductivity are observed. Recent progress and important approaches adopted for overcoming and alleviating these drawbacks are described in this article. A perspective on these matters is suggested and the requirements for each material are delineated, in addition to introducing a full‐cell prototype utilizing a Li‐rich cathode and Si anode.